Proses Pembuatan Beton Dengan Mutu K-350 Pada Mesin Batching Plant Wet Mix di PT. Prima Beton Nusantara - Sultan Abdillah; Nadjmudin Fauji (Peneliti.net, 2022)
The purpose of this study was to obtain the results of the Fresh Concrete Production Process at the Batching Plant Machine at PT Prima Beton Nusantara. Concrete production process at PT. The SBU Prima Beton is a production that is quite widely used by other PTs. From the report above, several conclusions can be drawn, namely: 1) The concrete production process using a batching plant machine is the thing that is most widely used by companies that make large amounts of concrete because of its efficiency. which is quite good and fast., 2) The stirring process is one of the main things in the process of making concrete., 3) The production process using the Batcing Plant Machine is enough to affect the quality of the concrete produced, 4) on the results of the compressive strength test, getting the greatest compressive strength in sample 2 with a compressive strength test for 28 days with a compressive strength result of 360.31 kg/cm2 or 102.95% of the standard required compressive strength value. Meanwhile, the lowest compressive strength value is found in sample 2 with a compressive strength test for 3 days with a compressive strength result of 176.68 kg/cm2 or 50.48% of the standard required compressive strength value.